Organic-Based fertilizers Produced from Sago Hampas and Decanter Cake and Their Uses in Maize (Zea Mays L.) Cultivation - DEBORAH RENTING, JIMMY (UNIMAS, 2025)
Sustainable agriculture requires innovative strategies to enhance soil fertility while reducing the environmental impacts of agro-industrial waste. This study investigated the synergistic effects of Black Soldier Fly (BSF) frass and decanter cake (DC) biochar on maize (Zea Mays L.) growth and soil fertility in tropical acidic soil. BSF larvae were used to bioconvert sago hampas and DC into nutrient-rich frass, while DC was pyrolyzed to produce biochar. Laboratory incubation and pot experiments were conducted with eight treatments: control (F0B0C0), 100% chemical fertilizer (F0B0C1), 100% BSF frass alone (F1B0C0), 100% biochar alone (F0B1C0), 50% frass + biochar + chemical fertilizer (F2B2C2), 50% frass + chemical fertilizer (F2B0C2), 50% biochar + chemical fertilizer (F0B2C2), and 50% frass + biochar (F2B2C0). Soil chemical properties, nutrient availability, and maize biomass were assessed after 52 days. Results showed that the combined application of frass and biochar significantly improved soil pH, cation exchange capacity, and nutrient retention compared to untreated soil. The integrated treatment (F2B2C2) recorded the highest improvements, with a 41% increase in total nitrogen, 58% enhancement in phosphorus, 22% improvement in potassium, and a 37% increase in zinc relative to the control. These nutrient enhancements translated into the highest maize dry weight among treatments. The study concludes that BSF frass and DC biochar, particularly in combination with reduced chemical fertilizers, enhance nutrient-use efficiency, sustain soil fertility, and improve maize productivity. This integrated approach valorizes agro-industrial wastes, reduces dependence on synthetic inputs, and contributes to sustainable tropical agriculture.